Court-Connected Mediation: Resolution of Civil Disputes Based on The Principle of Deliberation - Indriati Amarini; Noor Kholifah Hidayati; Izzatul Muna (Jurnal Hukum dan Peradilan, 2026)
Mediation is a method for peacefully resolving disputes. In Indonesia, mediation has been part of the court dispute resolution process since the introduction of the Dutch East Indies court procedural law. The Supreme Court has since reinforced mediation through regulations to facilitate early dispute resolution. However, the practical application of mediation in courts has not reached its full potential. This research examines the court mediation model in light of Pancasila values. The study employs doctrinal research methods and analyzes secondary data, including laws, regulations, books, research findings, and academic journals, through qualitative analysis. Findings indicate that disputes are ideally resolved through deliberation, with court proceedings a last resort. Mediation aligns with Pancasila's philosophical foundations, emphasizing consensus-building through deliberation. This principle is crucial for national life and governance and is grounded in the Pancasila value of democracy guided by wise deliberation and representation. Court mediation, reflecting Pancasila values, involves a neutral third party, typically a judge, to facilitate a fair resolution, aiming not only for agreement but also for harmony, unity, and justice among the conflicting parties.